A Atuação da auditoria interna nas universidades federais brasileiras - Rodrigues, Rubens Carlos (2017)
Credibility in the information generated by the Internal Control System (ICS) is essential for management and, in order to verify the functioning of the existing control mechanisms in the institutions, the Internal Audit units have been established, which are an important tool for managers and other interested parties. These units aim not only at attesting to the legality but also to the efficiency of management's actions, however, the control over the results to be achieved and advice to management has been highlighted. Considering that these units can not verify all existing processes and documentation in the institutions, it is necessary to plan the activities to be carried out, analyzing the risks and the evaluation of the existing controls. In view of this scenario, this research aims to evaluate the activities carried out in 2016 by the Internal Audit in the scope of the Brazilian Federal Public Universities in compliance with the established by the control bodies. Regarding the methodology, this research can be defined as to the objectives, of the descriptive type; as to the procedures to be adopted, documentary, and regarding the approach to the research problem, qualitative. The data necessary for its realization were obtained through the Information Access Law (LAI), the Annual Internal Audit Activities Plan (PAINT) and the Annual Report of Internal Audit Activities (RAINT), which were organized and tabulated by means of Excel® software, thus enabling the agglutination of the data and the construction of tables, graphs and descriptive statistics for later realization of the evaluation and interpretation of the findings. The results obtained demonstrate that there are Internal Audit units installed in 61 of the 63 universities surveyed. The functional body is formed by contest servants who are trained in the area of Administration, Accounting or Law Sciences and postgraduate. The activities developed are aimed at Management Controls and are mainly focused on management and operational audits. More than a third of the activities are related to advice and guidance to managers, follow-up of the implementation of recommendations of the internal / external control bodies and issuance of reports promoting active transparency by this unit